Periodized combined training in physically active overweight women over 50 years - Thaís Mara Alexandre Bertazone; Leonardo Henrique de Lima Medeiros; Célia Ignácio de Oliveira; Carlos Roberto Bueno Junior; Angelita Maria Stabile (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This quasi-experimental study, analyzes if periodized combined training's influence on plasma cytokine levels, muscle strength, and cardiorespiratory fitness in physically active women with overweight and/or obesity over 50 years. Methods: The sample was composed of 33 physically active women who were randomly allocated to three groups: Non-Periodized (NP) (n = 11); Undulating Periodization (UP) (n = 9); and Flexible Undulating Periodization (FUP) (n = 13). This study was conducted for 17 weeks, which included adaptation (weeks 1-3), baseline testing (week 4), training program (weeks 5-16), and post-evaluation (week 17). The training frequency comprised of three weekly sessions, with 30 min of aerobic exercise and 45 min of strength exercises. The data were analyzed using descriptive statistics and analysis of variance. The level of significance was p ≤ 0.05. Results: No differences were observed in weight parameters, plasma levels of cytokines, and biochemical parameters in any group, before and after the completion of the training period. Participants demonstrated increase in strength of the upper limbs in the UP (p = 0.032) and FUP (p = 0.021) groups, an increase in aerobic fitness in the NP (p = 0.041) and UP (p = 0.005) groups, and an increase in the amount of time of vigorous activity per week in the NP group (p = 0.019). Conclusion: This study shows that periodized combined training in physically active women with overweight and/or obesity over 50 years proved to be beneficial for all groups; although, the UP group exhibited better performance.